The Impact Of Chatgpt Use On Efl Students’ Writing Ability - Siti Roisah; Titik Lina Widyaningsih; Yepi Sedya purwananti (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
Writing is an important English language skill for students to learn. As technology advances, Artificial Intelligence (AI) is becoming a significant trend with diverse applications. AI has penetrated various industries, including education. The emergence of artificial intelligence (AI), specifically ChatGPT, offers a new avenue to improve writing skills. ChatGPT with its capabilities will provide feedback and support in generating ideas in writing. This study aims to see whether there is a significant influence on the writing ability of grade XI students after using ChatGPT at SMAN 1 Karangrejo. This study used an experimental quantitative method for data collection. The participants of this study were 60 eleventh-grade students, 30 students from class XI-D (control class), and 30 students from class XI-E (experimental class). The instrument in this study was a test, namely a pre-test conducted before treatment, and a post-test conducted after treatment. In analyzing the data, the researcher used the t-test method on the SPSS program. The results showed that students who used ChatGPT had an improvement in writing compared to students who were taught with the usual method. This is proven by the significance value of 0.00<0.05, which means that there is a significant difference in the initial and final scores of students who were given the treatment of using ChatGPT for the writing process. Based on this, it can be concluded that ChatGPT significantly affects the writing ability of eleventh-grade students of SMAN 1 Karangrejo.